A Review of Adolescent Behavior Against Lesbian, Gay, Bisexual, Transgender (LGBT) Behavior at SMA Negeri 5 Pekanbaru - Hamidah Sari Batubara; Andriani (International Journal of Public Health Excellence (IJPHE), 2022)
LGBT behavior is a form of negative behavior because this behavior is seen as inconsistent with the norms prevailing in society. On average, a lesbian is aware of his homosexuality since he was a teenager. In his research, three general factors were found in the formation of sexual identity in adolescents. This study aims to describe the behavior of adolescents towards lesbian, gay, bisexual, transgender (LGBT) behavior in SMA Negeri 5 Pekanbaru in 2018. Type of quantitative research with a descriptive design. The population in this study were all 829 students at SMA Negeri 5 Pekanbaru with a sample of 89 people. The data was collected using the stratifield proportional random sampling method. The data were processed in a univariate way. The results obtained from the knowledge of the majority of adolescents have sufficient knowledge, amounting to 68 people (76%), the attitude of the majority of adolescents is negative 56 people (63%) and the majority of adolescent actions do not do 71 people (80%). For future researchers to be able to carry out further research such as factors that influence adolescent behavior or quantitative research with analytic designs at SMA Negeri 5 Pekanbaru.